A Prospective Antimicrobial Prescription Audit in the Inpatient Department of Pulmonology in a Tertiary Care Hospital: Pharmaceutical Science-Pharmacy practice for good health promotion - Arul Prakasam; Abhirami Jayachandran; Archana M Nair; Asmina Sherin Hazankutty; Pooja Chandran (International Journal of Life Science and Pharma Research, 2022)
Antibiotics are medicines used to prevent and treat bacterial infections. Antibiotic usage is increasing rapidly day by day with or without prescription. Irrational prescription usage, negligence of standard guidelines and antimicrobial resistance are increasing complexity in the therapy and the desired outcome. High-volume prescription of antibiotics in primary health care is a major factor contributing to antibiotic resistance. Educating physicians and patients can lower prescribing errors and the aim of this study was to do a prospective observational prescription audit in inpatient department of pulmonology in a tertiary care hospital and limiting the inappropriate use of antimicrobials. The primary objective of the study is to determine the Antibiotic prescription, find out the inappropriate drug selection, dose selection, dosage form and course of antibiotics to monitor the culture test as well as antibiotic sensitivity and resistance and also to analyze the drug interaction, allergic medication prescribed and omission of the dose. The study was conducted with 234 patients in Erode district, Tamilnadu. The study conducted by strictly observing the antimicrobial prescription in the inpatient pulmonology department in a tertiary care hospital, limiting the inappropriate drug selection, dose selection, dosage form, course of antibiotics and hence decreasing the antibiotic resistance. The prescribing and administering details were collected in a data acquisition form; the collected data were interpreted with Sanford and GOLD Standard Guidelines and analyzed with descriptive statistics. The study found that irrational use of medication was high (53.41%) and a highly significant medication error also reported. The major concomitant disorder was Chronic Obstructive Pulmonary Disorder (21.79%) and most administered drug was Ceftriaxone (20.51%) (Third generation Cephalosporins). Culture test (32.90%) as well as antibiotic sensitivity and resistance test were done in very less cases, empirical therapy dominates over targeted therapy which affects rationality.